2011
DOI: 10.1073/pnas.1117772108
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β and 17β-hydroxysteroid dehydrogenase type 6, a growth regulatory pathway that is lost in prostate cancer

Abstract: Estrogen receptor β (ERβ) is activated in the prostate by 5α-androstane-3β,17β-diol (3β-Adiol) where it exerts antiproliferative activity. The proliferative action of the androgen receptor is activated by 5α-dihydrotestosterone (DHT). Thus, prostate growth is governed by the balance between androgen receptor and ERβ activation. 3β-Adiol is a high-affinity ligand and agonist of ERβ and is derived from DHT by 3-keto reductase/3β-hydroxysteroid dehydrogenase enzymes. Here, we demonstrate that, when it is expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…In contrast, estrogen was unable to stimulate PHD2 expression. These data support previous studies indicating that 3β-adiol, but not estrogen, promotes an epithelial phenotype in prostate cells (9,16,17). It is worth noting, however, that the PHD1 (EGLN2) gene is estrogen inducible in breast carcinoma cells (41).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In contrast, estrogen was unable to stimulate PHD2 expression. These data support previous studies indicating that 3β-adiol, but not estrogen, promotes an epithelial phenotype in prostate cells (9,16,17). It is worth noting, however, that the PHD1 (EGLN2) gene is estrogen inducible in breast carcinoma cells (41).…”
Section: Discussionsupporting
confidence: 77%
“…In pursuit of a functional basis for this relationship, we demonstrated that ERβ sustains an epithelial phenotype and impedes a mesenchymal transition in prostate cancer and we identified a metabolite of dihydrotestosterone, 5α-androstane-3β,17β4-diol (3β-adiol) as the specific ERβ ligand that mediates this function (9). This observation is in agreement with the recent findings that 3β-adiol is a natural ligand for ERβ in prostate (13,(15)(16)(17).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Aging male ERβ −/− mice developed prostate hyperplasia and prostatic intraepithelial neoplasia (PIN), a premalignant stage of adenocarcinoma (8). ERβ is also expressed in normal human prostate and in prostate cancer of Gleason grades up to 3 + 3 but its expression decreases as cancer progresses (9)(10)(11). The loss of ERβ expression during the progression from high-grade PIN to cancer suggests that ERβ may act as a tumor suppressor.…”
mentioning
confidence: 99%
“…Both receptors are located in the prostate glands and they have been postulated to have important effects on these glands (Harkonen et al, 2004). Many previous studies have investigated the relation between genes that are involved in the estrogen metabolism pathway and the risk of prostate carcinoma (Celhay et al, 2010;Muthusamy et al, 2011). Variants on the gene ER alpha (ESR1) have been reported to be significantly associated with the risk of other sex steroid hormone-related carcinomas, such as breast cancer (Li et al, 2010), endometrial cancer (Einarsdottir et al, 2009) and ovarian carcinoma (Doherty et al, 2010).…”
Section: Introductionmentioning
confidence: 99%